Soil electrical conductivity as a proxy for enhanced weathering in soils - Rieder, Lukas; Amann, Thorben; Hartmann, Jens (Frontiers in Climate, 2024)
To effectively monitor and verify carbon dioxide removal through enhanced weathering (EW), this study investigates the use of soil electrical conductivity (EC) and volumetric water content (θ) as proxies for alkalinity and dissolved inorganic carbon (DIC) in soil water. EC-θ sensors offer a cost-effective and straightforward alternative to traditional soil and water sampling methods. In a lab experiment, three different substrates were treated with NaHCO3 solutions to increase the alkalinity of the soil water and analyze the response. The combination of EC and θ to track the increase in carbonate alkalinity due to EW, and therefore CO2 consumption, is applicable for low cation exchange capacity (CEC) soil-substrates like the used quartz sand. However, the presence of organic material and pH-dependent CEC complicates the detection of clear weathering signals in soils. In organic-rich and clay-rich soils, only a high alkalinity addition has created a clear EC signal that could be distinguished from a non-alkaline baseline with purified water. Cation exchange experiments revealed that the used soil buffered alkalinity input and thereby might consume freshly generated alkalinity, initially mitigating CO2 uptake effects from EW application. Effective CEC changes with pH and pH buffering capacity by other pathways need to be considered when quantifying the CO2 sequestration potential by EW in soils. This should be estimated before the application of EW and should be part of the monitoring reporting and verification (MRV) strategy. Once the soil-effective CEC is raised, the weathering process might work differently in the long term.